2015
DOI: 10.3109/02770903.2015.1065421
|View full text |Cite
|
Sign up to set email alerts
|

Limited treatment adaptation despite poor asthma control in asthma patients treated with inhaled corticosteroids

Abstract: Asthma was unacceptably controlled in most patients receiving ICS-containing maintenance treatment and remained so during follow-up. Despite this, treatment adaptations by GPs and CPs were very infrequent. This unsatisfactory situation may be improved by adopting a more dynamic approach to tailoring controller therapy to the needs of the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…One of the sociodemographic factors most strongly associated with asthma control was gender in our study: men were more likely than women to have controlled asthma, as previously reported [19,26,27]. One possible explanation is that women are more prone to severe asthma than men [28].…”
Section: Discussionsupporting
confidence: 71%
“…One of the sociodemographic factors most strongly associated with asthma control was gender in our study: men were more likely than women to have controlled asthma, as previously reported [19,26,27]. One possible explanation is that women are more prone to severe asthma than men [28].…”
Section: Discussionsupporting
confidence: 71%
“…According to a study called the National Asthma Survey conducted in the USA, asthma control was found to be higher in men and young people [17,18]. In many studies, it has been stated that gender affects asthma control, and it is more uncontrolled in women than in men [19,20]. In our study, it was determined that the gender factor was not important, and the age factor was found to be compatible with the literature.…”
Section: Discussionsupporting
confidence: 83%
“…However, studies have shown that patients with low asthma control, often do not have their treatment adapted to meet their needs despite regular follow up. A study in France found that most of the patients recruited experienced poor asthma control despite receiving regular maintenance treatment, and remained so during followup visits, yet treatment adaptations were very infrequent [31]. Regular, scheduled follow-up visits where asthma control is assessed and therapy is tailored to the individual needs of the patient could improve asthma control in the Middle East and throughout the world.…”
Section: Discussionmentioning
confidence: 99%